Coping with a dual shock : the economic effects of COVID-19 and oil price crises on African economies - (:unkn) unknown (My University, 2021)
Oil-dependent countries face a twin-shock: in addition to the COVID-19 outbreak, they are facing an oil price collapse. In this paper, we study the impact of this dual shock on the forecasted GDP growth in Africa using the COVID-19 outbreak as a natural experiment. We use the IMF World Economic Outlook’s GDP growth forecasts before and after the outbreak. We find that COVID-19 related deaths result in -2.75 percentage points forecasted GDP growth loss in the all sample while oil-dependence induces -7.6 percentage points loss. We document that the joint shock entails higher forecasted growth loss in oil-dependent economies (-10.75 percentage points). Based on oil price forecasts and our empirical findings, we identify five recovery policies with high potential: social safety net policy, economic diversification, innovation and technological transformation, fiscal discipline, and climate-friendly recovery policy.
Keywords: African Research